Construction of N-M Interaction Diagram for Reinforced Concrete Columns Strengthened with Steel Jackets Using Plastic Stress Distribution Method - Al-Sherrawi, Mohannad Husain; Salman, Hamza M. (Salehan Institute of Higher Education, 2017)
No attempts have been made in developing the N-M interaction diagram for reinforced concrete columns strengthened with steel jackets using the plastic stress distribution method. Therefore, this paper presents an analytical model to construct the N-M interaction diagram for reinforced concrete columns strengthened with steel jackets using the plastic stress distribution method after assuming the behavior of strengthened column to be like composite column and including the effects of confinement on concrete compressive strength. The proposed model was compared with experimental results. The comparisons showed that the model is conservative and it reveals the ultimate strength of the strengthened column. A parametric study has been also carried out to investigate the influence of various parameters on the N-M interaction diagram of the strengthened column. These parameters were: dimensions of steel angle, yield stress of the steel angles, concrete compressive strength and the size of the reinforcement bars used in RC columns. The results made clear the effects of these parameters on the N-M interaction diagram, and encouraged the use of the model in preliminary strengthening studies.